ISOTROPIC GEOMETRY OF GRAPH SURFACES ASSOCIATED WITH PRODUCT PRODUCTION FUNCTIONS IN ECONOMICS - Aydin, Muhittin Evren; Ergut, Mahmut (Tamkang Univ, 2016)
A production function is a mathematical formalization in economics which denotes the relations between the output generated by a firm, an industry or an economy and the inputs that have been used in obtaining it. In this paper, we study the product production functions of 2 variables in terms of the geometry of their associated graph surfaces in the isotropic 3-space I-3. In particular, we derive several classification results for the graph surfaces of product production functions in I-3 with constant curvature.
Keywords: Production function; return to scale; relative curvature; isotropic mean curvature; isotropic space